2019
DOI: 10.3390/bs9120117
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of Guilt Appeals: A Review Showing the Importance of Investigating Cognitive Processes as Mediators between Emotion and Behavior

Abstract: Guilt appeals in the field of persuasion are quite common. However, the effectiveness of these messages is sometimes ambivalent. It is widely acknowledged that guilt leads people to engage into prosocial behaviors, but the effects of guilt can also be counter-productive (e.g., reactance-like effects). We argue that the explanations for these contradictions remain unsatisfactory and suggest that taking into account the implications of underlying cognitive—especially attentional—mechanisms would provide a better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…With that in mind, however, the use of guilt appeals has been shown in certain cases to backfire by inducing psychological reactance (e.g., Graton & Mailliez, 2019). These findings, coupled with the prevalence of guilt appeals in prosocial campaigns, emphasize the need to further explore the boundary conditions of guilt's influence.…”
Section: Guilt As a Persuasive Appealmentioning
confidence: 99%
See 1 more Smart Citation
“…With that in mind, however, the use of guilt appeals has been shown in certain cases to backfire by inducing psychological reactance (e.g., Graton & Mailliez, 2019). These findings, coupled with the prevalence of guilt appeals in prosocial campaigns, emphasize the need to further explore the boundary conditions of guilt's influence.…”
Section: Guilt As a Persuasive Appealmentioning
confidence: 99%
“…Despite evidence indicating that guilt can powerfully affect attitudes and behavior (e.g., Boster et al, 2016; Xu & Guo, 2018), there is still considerable ambiguity regarding when and how guilt influences prosocial outcomes. As suggested in a recent review of the guilt literature, “A wide body of research has focused on [guilt's] definition and behavioral consequences…however, there is a lack of knowledge regarding the processes linking guilt to prosocial actions” (Graton & Mailliez, 2019; p. 117). Specifically, two outstanding questions remain surrounding the identity conditions that (a) induce guilt (personal vs. collective) and (b) encourage individuals to act upon guilt (self‐ vs. collective‐efficacy).…”
Section: Introductionmentioning
confidence: 99%
“…For example, controlling language in promotional health messages increased the perceptions of anger (Miller et al, 2007), and messages overtly discouraging smoking among young adults can backfire and increase the likelihood of engaging with smoking behaviors (Grandpre et al, 2003). Additionally, health-related communications appealing to guilt have been shown to increase feelings of anger (Coulter & Pinto, 1995), reduce HPV vaccination intentions (Carcioppolo et al, 2017), and increase the likelihood of message rejection (Graton & Mailliez, 2019). Such negative behavioral outcomes or rejection of messages may be attributed to psychological reactance, which is a motivated state serving to restore perceived threats to personal freedom (Brehm, 1966).…”
Section: Known Predictors Of Flu Vaccination Uptakementioning
confidence: 99%
“…Hence, one can change behaviour in order to reduce the feeling of guilt. Contrary to shame, the action tendencies typically associated with guilt are approach and reparative behaviour (Amodio et al, 2007;Graton & Mailliez, 2019;Graton & Ric, 2017). However, Amodio et al's (2007) suggested that there are two stages in the temporal development of guilt-induced behavioural tendencies.…”
Section: Shame and Guilt As Potential Moderatorsmentioning
confidence: 99%